(untitled) (MAUSAM, 1984)
Ships. data collected during the sixties have been processed and analysed by IBM- 360 system. A fresh attempt has been made towards the evaluation of evaporation, sensible and latent heat transport, Bowen ratio values and the transfer of total heat energy to atmosphere from the Indian Ocean, the Arabian Sea and the Bay of Bengal.